Index Finger Muscle Fatigue and Pistol Firing Failure. (November 2019) - Nestler, Kai; Rohde, Ulrich; Witzki, Alexander; Waldeck, Stephan; Becker, Benjamin; Leyk, Dieter
Objective: The aim of this study was to analyze finger strength and effects of muscle fatigue on the ability to shoot. Background: The finger and hand muscles of soldiers are subject to high loads. For example, the trigger pull of military pistols can amount up to 58 N (≈6 kg) and could cause muscle fatigue in the trigger finger. For soldiers, however, maintaining the ability to shoot is essential for self-defense and survival. Method: The marksmanship training of 30 German soldiers (15 female) ages 18 to 40 years was evaluated. Three consecutive exercises with a total of 60 rounds were fired from target ranges of 5 and 10 m, equally using a single-action and double-action trigger mode. Maximum voluntary isometric contraction of the index finger (MVCIF ) was measured before and after each of the three firing exercises. Results: Shooting reduced MVCIF in female (88.2 ± 15.8 N to 67.3 ± 17.7 N, p < .001) and male soldiers (145.8 ± 21.7 N to 112.7 ± 26.6 N, p < .001). Of the 30 subjects, 23 were unable to shoot due to fatigue, including 15 of 15 female soldiers. The higher MVCIF was at rest, the less commonly ( r = .73, p < .001) and the later ( r = 0.82, p < .001) task failure occurred. Two intermissions of approximately 6 min did not suffice for a significant recovery. Conclusion: Excessive trigger pull weight causes muscle fatigue of the index finger and can ultimately lead to task failure during pistol marksmanship training. Short breaks are insufficient for the recovery of finger muscles. Application: This study presents a new perspective on ideal trigger pull weight, which should be carefully considered by manufacturers to allow repetitive firing and simultaneously ensure safe handling.